Transforming Growth Factor-β Signaling Pathway in Patients With Kawasaki Disease - Shimizu, Chisato; Jain, Sonia; Davila, Sonia; Hibberd, Martin L.; Lin, Kevin O.; Molkara, Delaram; Frazer, Jeffrey R.; Sun, Shelly; Baker, Annette L.; Newburger, Jane W.; Rowley, Anne H.; Shulman, Stanford T.; et al. (Circulation. Cardiovascular genetics, 2011)
BACKGROUND—Transforming growth factor (TGF)-β is a multifunctional peptide that is important in T-cell activation and cardiovascular remodeling, both of which are important features of Kawasaki disease (KD). We postulated that variation in TGF-β signaling might be important in KD susceptibility and disease outcome. METHODS AND RESULTS—We investigated genetic variation in 15 genes belonging to the TGF-β pathway in a total of 771 KD subjects of mainly European descent from the United States, the United Kingdom, Australia, and the Netherlands. We analyzed transcript abundance patterns using microarray and reverse transcriptase–polymerase chain reaction for these same genes, and measured TGF-β2 protein levels in plasma. Genetic variants in TGFB2, TGFBR2, and SMAD3 and their haplotypes were consistently and reproducibly associated with KD susceptibility, coronary artery aneurysm formation, aortic root dilatation, and intravenous immunoglobulin treatment response in different cohorts. A SMAD3 haplotype associated with KD susceptibility replicated in 2 independent cohorts and an intronic single nucleotide polymorphism in a separate haplotype block was also strongly associated (A/G, rs4776338) (P=0.000022; odds ratio, 1.50; 95% confidence interval, 1.25 to 1.81). Pathway analysis using all 15 genes further confirmed the importance of the TGF-β pathway in KD pathogenesis. Whole-blood transcript abundance for these genes and TGF-β2 plasma protein levels changed dynamically over the course of the illness. CONCLUSIONS—These studies suggest that genetic variation in the TGF-β pathway influences KD susceptibility, disease outcome, and response to therapy, and that aortic root and coronary artery Z scores can be used for phenotype/genotype analyses. Analysis of transcript abundance and protein levels further support the importance of this pathway in KD pathogenesis.